Implementasi Kebijakan Sistem Zonasi pada Penerimaan Peserta Didik Baru (PPDB) Sebagai Upaya Pemerataan Pendidikan di SMA Negeri Kabupaten Gresik - Sri Lestari, Novi; Hanafi, Imam; Mardiyono, Mardiyono (Jurnal Ilmiah Administrasi Publik, 2024)
The zoning system policy of New Learner Admission (PPDB) refers to the division of administrative areas into certain zones, where prospective learners will be placed based on the location of their residence. the zoning system policy is carried out by the Gresik Regency Government to provide equal access to education and ensure that every learner has equal access to education.  The uneven distribution of public senior high schools in Gresik Regency can cause difficulties in accessing education for students. This condition leads parents to take actions such as entrusting their child's name to the Family Card (KK) of family or friends who live close to the location school. There are also those who deliberately manipulate the coordinates of the house to make it look closer to the location of the location school. The purpose of this study is to describe and analyze the implementation of the zoning system policy in the admission of New Learners (PPDB) as an effort to equalize education in public high schools in Gresik Regency.  The research method used is descriptive qualitative research method. Data collection techniques are interviews, observation and documentation. The results showed that the policy has been running well according to the variables proposed by George C. Edwards III. Communication is done by providing socialization to schools and parents of students. The resources used are in accordance with the required capabilities. Disposition, the local government supports the zoning system policy. Bureaucratic structure, namely the formation of a special PPDB committee in each high school.